Predicted soil water isotopes from West Africa (Benin and Senegal) using Craig and Gordon evaporation model and a mixing equation - Anne Alexandre (PANGAEA, 2025)
Simple evaporation model applied to a layer of soil water defined as an isolated volume of water (cf Criss, 1999, Surma et al., 2015 and Voigt et al., 2021 for definition of the parameters). The isotope composition of the initial water considered is that of the main precipitation preceding the coring. Atmospheric relative humidity and air temperature considered are the diurnal averages (for the period from August 18 to August 24, 2019 at DA). Pure molecular diffusion (wind coefficient of 1) is assumed.
In: Alexandre, A (2025): Climate and triple oxygen isotope of precipitation, groundwater, soil water, plant water, and phytolith data from West Africa (Benin and Senegal) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984133